2020
DOI: 10.1055/s-0040-1712984
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning a Practice to Robotic Total Knee Arthroplasty Is Correlated with Favorable Short-Term Clinical Outcomes—A Single Surgeon Experience

Abstract: Background This study sought to evaluate the patient experience and short-term clinical outcomes associated with the hospital stay of patients who underwent robotic arm-assisted total knee arthroplasty (TKA). These results were compared with a cohort of patients who underwent TKA without robotic assistance performed by the same surgeon prior to the introduction of this technology. Materials and Methods A cohort of consecutive patients undergoing primary TKA for the diagnosis of osteoarthritis by a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…1 ) [ 12 , 24 , 35 , 42 ]. A list of the 16 studies which met the inclusion criteria are illustrated in Table 1 [ 4 , 18 20 , 23 , 25 , 28 , 30 32 , 36 , 44 , 49 52 ]. Nine studies were identified from Medline and PubMed, and seven additional studies from Google Scholar (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ) [ 12 , 24 , 35 , 42 ]. A list of the 16 studies which met the inclusion criteria are illustrated in Table 1 [ 4 , 18 20 , 23 , 25 , 28 , 30 32 , 36 , 44 , 49 52 ]. Nine studies were identified from Medline and PubMed, and seven additional studies from Google Scholar (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported on the complications between RATKA and mTKA groups (Table 6 ) [ 4 , 19 , 20 , 25 , 36 , 49 ]. The most reported complications were arthrofibrosis requiring MUA, superficial or deep infections and wound dehiscence.…”
Section: Resultsmentioning
confidence: 99%
“…The time required to perform the robotic-specific surgery steps is similar to the time required for the setup and handling of the alignment guides and cutting blocks used to perform alignment during the conventional method. Previous studies have shown consistent findings [7,24], although two studies reported significantly longer surgery times for roboticassisted TKA [25,26].…”
Section: Discussionmentioning
confidence: 60%
“…The learning curve of the two studies focused on the first 10–15 patients, and the operative times of the remaining patients showed no difference. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…The RATKA group requires longer operative times in the early stages of surgery as surgeons required more time to learn and adapt to the new technique. Once they become proficient in COTKA, after adaptive learning and training of 20 cases, the time spent on RATKA should not be different from that of COTKA 28,29 . Fleischman et al 30 .…”
Section: Discussionmentioning
confidence: 99%